Childhood cancer and environmental integrity: a commentary and a proposal - Carlo Modonesi; Enrico Oddone; Celestino Panizza; Gemma Gatta
ABSTRACT Improvements in the health standards of developed and developing societies depend primarily on the relationships between economy and environment. Recent long-term changes in the chemical composition of man-made environments may be linked to changes in the biology of human beings. Here we argue that children are at the greatest risk of being affected by the dangerous effects of these changes, with particular reference to cancer. The concept of cancer risk must be extended to new contexts. Considering the increasing rates of chemical pollution and its spreading in the environment, we illustrate a proposal aiming to protect the human health, in an intra- and intergenerational perspective. A surveillance system of occupational and residential exposures should be implemented to prevent cancer risk in embryos and children.